DEEP LEARNING DALAM UPAYA MENINGKATKAN KOMPETENSI SOSIAL SISWA MELALUI PEMBELAJARAN IPS - Komariyah, Sustin (Jurnal Sosialita, 2025)
Abstract The deep learning approach in Social Studies education aims to enhance students' social competence through deep understanding, critical thinking skills, and more meaningful interactions. Deep learning-based learning encourages students to connect concepts with real-life experiences, collaborate in problem-solving, and develop a higher social awareness. This study uses a literature review method to analyze various theories and research findings related to the application of deep learning in social studies education. The study results indicate that deep learning can enhance students' social competencies through learner-centered teaching strategies, such as project-based learning, case analysis, and reflective discussions. In addition, the use of technology, such as digital simulations and interactive learning platforms, plays an important role in supporting the implementation of deep learning. However, there are several challenges in its implementation, such as teacher readiness and limited access to technology in some areas. Therefore, support from various parties, including the government, educational institutions, and the community, is needed to ensure the effective and sustainable implementation of deep learning in social studies education.   Key words: Deep Learning, Kompetensi Sosial, Pembelajaran IPS, Kecerdasan Buatan